The Movement Advantage in Famous and Unfamiliar Faces: A Comparison of Point-Light Displays and Shape-Normalised Avatar Stimuli. (September 2013) - Bennetts, Rachel J; Kim, Jeesun; Burke, Darren; Brooks, Kevin R; Lucey, Simon; Saragih, Jason; Robbins, Rachel A
Facial movement may provide cues to identity, by supporting the extraction of face shape information via structure-from-motion, or via characteristic patterns of movement. Currently, it is unclear whether familiar and unfamiliar faces derive the same benefit from these mechanisms. This study examined the movement advantage by asking participants to match moving and static images of famous and unfamiliar faces to facial point-light displays (PLDs) or shape-normalised avatars in a same/different task (experiment 1). In experiment 2 we also used a same/different task, but participants matched from PLD to PLD or from avatar to avatar. In both experiments, unfamiliar face matching was more accurate for PLDs than for avatars, but there was no effect of stimulus type on famous faces. In experiment 1, there was no movement advantage, but in experiment 2, there was a significant movement advantage for famous and unfamiliar faces. There was no evidence that familiarity increased the movement advantage. For unfamiliar faces, results suggest that participants were relying on characteristic movement patterns to match the faces, and did not derive any extra benefit from the structure-from-motion cues in the PLDs. The results indicate that participants may use static and movement-based cues in a flexible manner when matching famous and unfamiliar faces.